DYNAMICS OF STOCK PRICES IN THE SHARIA CAPITAL MARKET: THE IMPORTANT ROLE OF FINANCIAL FUNDAMENTAL ANALYSIS - Lestari, Ajeng; Hadi, Azizan (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2024)
Islamic capital market shows investment potential that investors are interested in. Therefore, investors must understand information regarding share prices, such as fundamental analysis (ROE, DER, EPS and ROS) that occurs from outside the company, before deciding to sell or buy these shares. There are differences in theory with the phenomena that occur today so further research is needed. The problem formulation is to determine the effect of fundamental analysis (ROE, DER, EPS and ROS on the share price of a company. This type of research uses quantitative methods. The data used is secondary data which is the publication of the company's financial reports. The population is all companies registered in The Jakarta Islamic Index for the 2019-2023 period consisted of 20 companies. The sample was determined using a purposive sampling method and 10 samples were obtained. From the statistical tests carried out, it was found that ROE partially had a significant effect on stock prices, DER partially had no significant effect on stock prices. EPS partially has a significant effect on stock prices, and ROS partially has a significant effect on stock prices. The research results simultaneously found that the variables ROE, DER, EPS and ROS as a whole have a significant effect on stock prices.